2001
DOI: 10.2514/atcq.9.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Air-Ground Integration Experiment

Abstract: This document is disseminated under the sponsorship of the U.S. Department of Transportation in the interest of information exchange. The United States Government assumes no liability for the contents or use thereof. The United States Government does not endorse products or manufacturers. Trade or manufacturer's names appear herein solely because they are considered essential to the objective of this report. This document does not constitute FAA certification policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A concept feasibility study of shared air-ground separation responsibility is reported in [DiMeo et al, 2001] and [Lozito et al, 2001]. ANSP had a conflict probe, while cockpit crew had CDTI with alerting logic and state-based trajectory predictors.…”
Section: (2) Mixed Air-ground Separation Responsibilitymentioning
confidence: 99%
“…A concept feasibility study of shared air-ground separation responsibility is reported in [DiMeo et al, 2001] and [Lozito et al, 2001]. ANSP had a conflict probe, while cockpit crew had CDTI with alerting logic and state-based trajectory predictors.…”
Section: (2) Mixed Air-ground Separation Responsibilitymentioning
confidence: 99%